2013
DOI: 10.1039/c2cs35361j
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from dinuclear lanthanide nano-magnets

Abstract: The quest for higher density information storage has led to the investigation of Single-Molecule Magnets (SMMs) as potential molecules to be applied in materials such as hard discs. In order for this to occur, one must first design metal complexes which can retain magnetic information at temperatures where these applications become possible. This can only be achieved through answering and understanding fundamental questions regarding the observed physical properties of SMMs. While mononuclear lanthanide comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
226
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(248 citation statements)
references
References 73 publications
11
226
0
Order By: Relevance
“…As the overall electronic structure of a Dy III ion is very sensitive to its coordination environment, minor changes in the ligand systems can significantly affect the magnetic properties of the complexes [15][16][17]. Most of the reports on Ln-based SMMs concentrated mainly on either changing the Ln ion keeping the ligand system constant [18][19][20] or changing the ligand but keeping the coordination environment around the Ln ion unchanged [8]. Only few studies are known where modification in the ligand system was done to tune the relaxation behavior in the complexes [21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the overall electronic structure of a Dy III ion is very sensitive to its coordination environment, minor changes in the ligand systems can significantly affect the magnetic properties of the complexes [15][16][17]. Most of the reports on Ln-based SMMs concentrated mainly on either changing the Ln ion keeping the ligand system constant [18][19][20] or changing the ligand but keeping the coordination environment around the Ln ion unchanged [8]. Only few studies are known where modification in the ligand system was done to tune the relaxation behavior in the complexes [21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of SMMs is that, even in the absence of an external magnetic field, they can preserve the magnetization for long period of time at low temperatures. After an extensive research on 3d metal complexes in the last decade [2][3][4], a rapid development of Ln based SMMs has been observed in recent years [5][6][7][8][9]. Compared to 3d metals, Ln based SMMs are mostly investigated owing to the fact that the Ln III ions such as Dy III , Tb III , Er III , and Ho III have huge and unquenched orbital angular momentum [10][11][12] which causes substantial magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, dinuclear Ln III SMMs are very important model systems to answer basic questions regarding single-ion relaxation vs. slow magnetic relaxation arising from the molecule as an entity. Thus, Ln III 2 complexes are highly desirable [10][11][12][13][14][15][16][17][18][19][20]. Another interesting area to which dinuclear lanthanide(III) complexes (and also mononuclear ones) are relevant is quantum computation; Ln III ions are promising candidates for encoding quantum information [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Dinuclear complexes represent the simplest molecular entities which allow the study of magnetic interactions between Ln III spin carriers [10]. By studying such systems, researchers could expect to understand the nature and strength of Ln III ··· Ln III exchange interactions, as well as possible alignment of spin vectors and anisotropy axes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large unquenched orbital angular momentum, Ln III ions can exhibit large single-ion magnetic anisotropies, leading to significant energy barriers in lanthanide-based SMMs. [2][3][4] Therefore, the synthesis and characterization of high-nuclearity 3d-4f SMMs have attracted intensive attention in recent years. [5][6][7][8][9] Although many studies on 4f-4f or 3d-3d interactions have been reported, [10][11][12][13][14][15][16][17] research on 3d-4f exchange interactions is less developed.…”
Section: Introductionmentioning
confidence: 99%